Factors associated with mortality in patients with COVID‐19 admitted to intensive care: a systematic review and meta‐analysis. (29th June 2021) - Taylor, E. H.; Marson, E. J.; Elhadi, M.; Macleod, K. D. M.; Yu, Y. C.; Davids, R.; Boden, R.; Overmeyer, R. C.; Ramakrishnan, R.; Thomson, D. A.; Coetzee, J.; Biccard, B. M.
Summary: Identification of high‐risk patients admitted to intensive care with COVID‐19 may inform management strategies. The objective of this meta‐analysis was to determine factors associated with mortality among adults with COVID‐19 admitted to intensive care by searching databases for studies published between 1 January 2020 and 6 December 2020. Observational studies of COVID‐19 adults admitted to critical care were included. Studies of mixed cohorts and intensive care cohorts restricted to a specific patient sub‐group were excluded. Dichotomous variables were reported with pooled OR and 95%CI, and continuous variables with pooled standardised mean difference (SMD) and 95%CI. Fifty‐eight studies (44, 305 patients) were included in the review. Increasing age (SMD 0.65, 95%CI 0.53–0.77); smoking (OR 1.40, 95%CI 1.03–1.90); hypertension (OR 1.54, 95%CI 1.29–1.85); diabetes (OR 1.41, 95%CI 1.22–1.63); cardiovascular disease (OR 1.91, 95%CI 1.52–2.38); respiratory disease (OR 1.75, 95%CI 1.33–2.31); renal disease (OR 2.39, 95%CI 1.68–3.40); and malignancy (OR 1.81, 95%CI 1.30–2.52) were associated with mortality. A higher sequential organ failure assessment score (SMD 0.86, 95%CI 0.63–1.10) and acute physiology and chronic health evaluation‐2 score (SMD 0.89, 95%CI 0.65–1.13); a lower PaO2 :FI O2 (SMD −0.44, 95%CI −0.62 to −0.26) and the need for mechanical ventilation at admission (OR 2.53, 95%CI 1.90–3.37) were associated with mortality. Higher white cell counts (SMD 0.37, 95%CI 0.22–0.51); neutrophils (SMD 0.42, 95%CI 0.19–0.64); D‐dimers (SMD 0.56, 95%CI 0.43–0.69); ferritin (SMD 0.32, 95%CI 0.19–0.45); lower platelet (SMD −0.22, 95%CI −0.35 to −0.10); and lymphocyte counts (SMD −0.37, 95%CI −0.54 to −0.19) were all associated with mortality. In conclusion, increasing age, pre‐existing comorbidities, severity of illness based on validated scoring systems, and the host response to the disease were associated with mortality; while male sex and increasing BMI were not. These factors have prognostic relevance for patients admitted to intensive care with COVID‐19. 요약: 코로나‐19로 중환자실에 입원한 고위험 환자의 식별은 환 자 관리 전략에 도움이 될 수 있다. 본 메타분석의 목적은 데 이터베이스를 통해 2020년 1월 1일과 2020년 12월 6일 사이에 출판된 연구들을 검색하여 중환자실에 입원한 코로나‐19 성 인 환자들의 사망과 관련된 요인들을 확인하는 것이었다. 중 환자실에 입원한 코로나‐19 성인들에 대한 관찰 연구가 포함 되었다. 특정 환자 하위 그룹으로 국한된 혼합 코호트와 집중 치료 코호트에 대한 연구들은 제외되었다. 이분형 변수들은 전체 승산비(OR)와 95% CI가 보고되었고, 연속 변수들은 전 체 표준화된 평균 차이(SMD)와 95% CI가 보고되었다. 58건의 연구(44, 305명의 환자)가 문헌 고찰에 포함되었다. 연령 증가 (SMD 0.65, 95% CI 0.53‐0.77), 흡연(OR 1.40, 95% CI 1.03‐1.90), 고혈압(OR 1.54, 95% CI 1.29‐1.85), 당뇨(OR 1.41, 95% CI 1.22‐1.63), 심혈관계 질환(OR 1.91, 95% CI 1.52‐2.38), 호 흡기질환(OR 1.75, 95% CI 1.33‐2.31), 신장질환(OR 2.39, 95% CI 1.68‐3.40), 암(OR 1.81, 95% CI 1.30‐2.52)은 사망과 관련 이 있었다. 더 높은 순차적 장기 부전 평가(SOFA) 점수(SMD 0.86, 95% CI 0.63‐1.10)와 급성 생리 및 만성 건강 평가‐2 (APACHE‐2) 점수(SMD 0.89, 95% CI 0.65‐1.13); 낮은 PaO2 대 FiO2 (SMD ‐0.44, 95% CI ‐0.62 ‐0.26)와 입원 시 기계적 환기의 필요성(OR 2.53, 95% CI 1.90‐3.37)은 사망과 관련이 있었다. 더 많은 백혈구 수(SMD 0.37, 95% CI 0.22‐0.51), 호 중구(SMD 0.42, 95% CI 0.19‐0.64), D‐이합체(SMD 0.56, 95% CI 0.43‐0.69), 페리틴(철을 포함하는 단백질) (SMD 0.32, 95% CI 0.19‐0.45), 낮은 혈소판 수치(SMD ‐0.22, 95% CI ‐0.35 ‐0.10), 림프구 수(SMD ‐0.37, 95% CI ‐0.54 ‐0.19)는 모두 사망과 관련이 있었다. 결론적으로 연령 증가, 기존 동반 질환, 검증된 평정 시스템에 기반한 질병의 심각도, 질병에 대 한 숙주 반응은 사망과 관련이 있었다; 반면 남성 성별과 BMI 증가는 관련이 있지 않았다. 이러한 요인들은 코로나‐19로 중 환자실에 입원한 환자들에서 예후와 관련성이 있다.